Degree of risk for foot ulcer due to diabetes: nursing assessment - Maria do Livramento Saraiva Lucoveis; Mônica Antar Gamba; Maria Angela Boccara de Paula; Ana Beatriz Pinto da Silva Morita
ABSTRACT Objective: To classify the level of risk for foot ulcers in people with diabetes mellitus and identify their main predictive risk factors. Method: Exploratory, descriptive study, in which patients were assessed in a municipal ambulatory of São Paulo through nursing consultation, following the guidelines of the International Consensus on the Diabetic Foot. Data were descriptively analyzed. Results: The analyzed population was composed of 50 longevous and retired people, with household income of up to two minimum wages, with dermato-neurofunctional risk factors and unfavorable clinical indicators, and 66% had Risk 1; 16% Risk 2; 6% Risk 3 and 12% Risk 4. Of this analyzed total, 96% never had their feet examined with the Semmes-Weinstein monofilament. Conclusion: The data found indicate the importance of careful feet examination in people with diabetes by the nursing staff to identify future risks of ulcers and, thus, prevent them.